Dynamic Passivation in Perovskite Quantum Dots for Specific Ammonia Detection at Room Temperature. Issue 6 (21st January 2020) - Huang, Hui; Hao, Mingwei; Song, Yilong; Dang, Song; Liu, Xiaoting; Dong, Qingfeng
Abstract: Perovskite structured CsPbX3 (X = Cl, Br, or I) quantum dots (QDs) have attracted considerable interest in the past few years due to their excellent optoelectronic properties. Surface passivation is one of the main pathways to optimize the optoelectrical performance of perovskite QDs, in which the amino group plays an important role for the corresponding interaction between lead and halide. In this work, it is found that ammonia gas could dramatically increase photoluminescence of purified QDs and effectively passivate surface defects of perovskite QDs introduced during purification, which is a reversible process. This phenomenon makes perovskite QDs a kind of ideal candidate for detection of ammonia gas at room temperature. This QD film sensor displays specific recognition behavior toward ammonia gas due to its significant fluorescence enhancement, while depressed luminescence in case of other gases. The sensor, in turn‐on mode, shows a wide detection range from 25 to 350 ppm with a limit of detection as low as 8.85 ppm. Meanwhile, a fast response time of ≈10 s is achieved, and the recovery time is ≈30 s. The fully reversible, high sensitivity and selectivity characteristics make CsPbBr3 QDs ideal active materials for room‐temperature ammonia sensing. Abstract : Ammonia gas can effectively passivate surface defects of perovskite quantum dots with enhanced photoluminescence, which enables a specific recognition behavior toward ammonia at room‐temperature. The turn‐on mode sensor, with high sensitivity and selectivity, shows a fast and fully reversible response and a wide detection range and a limit of detection of 8.85 ppm.